Manganese Dynamics in Mouse Brain After Systemic MnCl2 Administration for Activation-Induced Manganese-Enhanced MRI - Tanihira, Hiroki; Fujiwara, Tomonori; Kikuta, Satomi; Homma, Noriyasu; Osanai, Makoto (Frontiers in Neural Circuits, 2021)
Activation-induced manganese-enhanced MRI (AIM-MRI) is an attractive tool for noninvasively mapping whole brain activities. Manganese ions (Mn2+) enter and accumulate in active neurons via calcium channels. Mn2+ shortens the longitudinal relaxation time (T1) of H+, and the longitudinal relaxation rate R1 (1/T1) is proportional to Mn2+ concentration. Thus, AIM-MRI can map neural activities throughout the brain by assessing the R1 map. However, AIM-MRI is still not widely used, partially due to insufficient information regarding Mn2+ dynamics in the brain. To resolve this issue, we conducted a longitudinal study looking at manganese dynamics after systemic administration of MnCl2 by AIM-MRI with quantitative analysis. In the ventricle, Mn2+ increased rapidly within 1 h, remained high for 3 h, and returned to near control levels by 24 h after administration. Microdialysis showed that extracellular Mn returned to control levels by 4 h after administration, indicating a high concentration of extracellular Mn2+ lasts at least about 3 h after administration. In the brain parenchyma, Mn2+ increased slowly, peaked 24-48 h after administration, and returned to control level by 5 days after a single administration and by 2 weeks after a double administration with a 24-h interval. These time courses suggest that AIM-MRI records neural activity 1-3 h after MnCl2 administration, an appropriate timing of the MRI scan is in the range of 24-48 h following systemic administration, and at least an interval of 5 days or a couple of weeks for single or double administrations, respectively, is needed for a repeat AIM-MRI experiment.